Parents’ Confidence Factors in Private and Public Educational Institutions - Miroshnikova, O.S. (Opción, 1970)
The article deals with the factor of user’s confidence in educational services as a condition for the creation of a positive image for private and public institutions. Based on theoretical analysis, a detailed description of the concept of confidence to an educational institution is given. The author describes the author’s method of identifying the features of confidence indicators. A comparative analysis of the criteria of confidence in different types of educational institutions is made. The differences in the real and ideal assessment of the organization in the public and private services sectors are revealed